The Obsolescence of Bureaucracy - Matejko, Alexander (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1980)
The bureaucratic model becomes more and more self-defeating in present time because it is highly inadequate to meet the challenges of the modem world. Literature on the alternative models of collective work is now available. These are also several highly encouraging practical experiences. Fewer and fewer people still trust that any substitute for bureaucracy is just unrealistic